Chronotope of Engineering and Pedagogical Thinking - A. V. Feoktistov; A. G. Kislov; I. V. Shapko; V. E. Gorodilov (Высшее образование в России)
The article is devoted to engineering and pedagogical thinking as a kind of professional thinking that exists due to specific reasons and necessary and sufficient conditions. The “assembly” of these causes and conditions takes place in a certain time-and-place (chronotope), the conceptual reconstruction of which opens the way to overcoming the traditions of haphazard enumerative descriptions of various properties that have developed in the literature and to reaching the construction of the theory of engineering and pedagogical thinking, which, in turn, will help to reasonably update the content and organization of training engineers-teachers, on whom a lot depends in the near technological future of Russia. A review of the characteristics of engineering-pedagogical and related engineering and pedagogical thinking presented in scientific publications is proposed. It shows the need for greater certainty in understanding the nature, foundations, essence and features of heterogeneous engineering and pedagogical thinking. Heterogeneity requires actualization of the potential not only of pedagogy and technical sciences, but also of philosophy, cultural studies, sociology, and psychology. Such actualization shows the heuristic of the communicative interpretation of the nature and essence of thinking. In its light, engineering-pedagogical thinking appears simultaneously as an articulated and unarticulated, discrete and continuous communication of engineers-teachers with students, within which the competencies required by the profession and the impulse developing engineering and technical flair and ingenuity are transmitted, “infecting” (V. Shklovsky2) and charging them, thanks to which communication overcomes the boundaries of the chronotope, gaining continuum features, demonstrating its pulsating situational-suprasituative (corpuscular-wave) dualism. The scientific novelty lies in the justification, by the example of advancing to the theory of engineering and pedagogical thinking, of supplementing the competence approach with consideration of no less significant cultural and subcultural factors, including latent ones, which sometimes manifest themselves in very weak signals about the features of the chronotope of training engineers and technicians by engineers–teachers, not so much by virtue of official regulations as by virtue of singular acts of everyday life communication.